POLITICAL DYNAMICS AT THE DAWN OF THE FOURTH DECADE OF SERBIAN MULTIPARTY SYSTEM - Simić, Savo (Political Review, 2023)
Edited book Thirty years since the restoration of multi-partyism in Serbia is a quality collection of political science papers on certain segments of electoral and political life in the Republic of Serbia. Indicatively, the title of the edited book refers to the treatment of an extensive chrono-political entity, which would initially lead some readers to form a conclusion about the overview of the entire Serbian multi-party era. In fact, hardly any scientific work could respond to the thematic and temporal challenge of the thirty-year political movement in Serbia. The organizers commendably included a sufficient number of authors from various scientific institutions in the preparation of the proceedings with considerable freedom in defining research topics. In addition, individual works of the collection offer a set of practical policies for modifying the shortcomings of the Serbian political system. In this regard, the works of Slobodan Zečević on the institutional design of the semi-presidential system and Milan Jovanović on the normative-electoral changes related to the parties of national minorities stand out. In the review, we briefly and evenly present the key results of the entire authorship, limited by the scope of this scientific form.
Keywords: political parties; multi-party sistem; Serbia; review